Analisis Risiko Kesehatan Lingkungan Dengan Risk Agent Total Suspended Particulate di Kawasan Industri Kota Probolinggo (Environmental Health Risk Assessment With Risk Agent Total Suspended Particulate In Industrial Area Probolinggo) - Amiratul Adila Ahmad; Khoiron Khoiron; Ellyke Ellyke (Pustaka Kesehatan, 2014)
The increase of economic development has made the industrialization and transportation became higher and they has been contributed to the increased of air pollution, include the Total Suspended Particulates (TSP). This research used descriptive methods with the purpose of analyzing the risk from risk agent for people who live in Rusunawa Bayuangga. A total of 70 samples age over 18 years were subjected to anthropometric surveys for body weight and particulate exposure. Data was collected by interview and direct measurement. Ambient air samples was taken just one point in resident ares and two points in industrial area with a moment method using a High Volume Air Sampler. The results were concentration of Total Suspended Particulate are between 0,0734 - 0.24 mg/m3. Exposure assessment revealed that TSP intake was safe since the calculated were under maximal intake 0,0082 mg/kg/day. Based on risk characterization result, it can be concluded that level of total risk was less than unity so it implies that in those area was safe for daily activities but there was a possibility of non-carcinogenic risk after exposure for 10 years (RQ ≥ 1). The advices of this research is planting of crops that can reducing the concentration of pollutants in the air such as Kembang sepatu, Tanjung and Kiara Payung. Keywords: Environmental Health Risk Assessment, Total Suspended Particulate